Treating Cocaine Addiction, Obesity, and Emotional Disorders by Viral Gene Transfer of Butyrylcholinesterase - Brimijoin, Stephen; Gao, Yang; Geng, Liyi; Chen, Vicky P. (Frontiers in Pharmacology, 2018)
Butyrylcholinesterase (BChE), a plasma enzyme that hydrolyses the neurotransmitter, acetylcholine relatively well, with far lower efficiency than acetylcholinesterase (AChE) but with the capability to degrade a broad range of bioactive esters. AChE is universally understood as essential to cholinergic neurotransmission, voluntary muscle performance, and cognition, among other roles, and its catalytic impact is essential for life. A total absence of BChE activity, whether by enzyme inhibition or simple lack of enzyme protein is not only compatible with life, but does not lead to obvious physiologic disturbance. However, very recent studies at Mayo Clinic have amassed support for the concept that BChE does have a true physiological role as a “ghrelin hydrolase” and, pharmacologically, as a cocaine hydrolase. Human subjects and animal mutations that lack functional BChE show higher than normal levels of ghrelin, an acylated peptide that drives hunger and feeding, along with certain emotional behaviors. Mice treated by viral gene transfer of BChE show higher plasma levels of enzyme and lower levels of ghrelin. Ghrelin is acknowledged as a key driver of food-seeking and stress. This brief review examines some key phenomena and considers means of modulating BChE as treatments for cocaine addiction, anxiety, aggression, and obesity.